2022
DOI: 10.1186/s13568-022-01348-3
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of antibacterial surfactin isoforms produced by Bacillus velezensis SK

Abstract: Bacillus velezensis SK having broad-spectrum antimicrobial activity has been isolated from soil. The efficient extraction of antimicrobial compounds produced in various mediums has been done using Diaion HP-20 resin. Further, characterization of an antimicrobial compound by TLC, FTIR, in-situ bioautography analysis revealed the presence of cyclic lipopeptides, which is then purified by the combination of silica gel, size exclusion, dual gradient, and RP-HPLC chromatography techniques. Growth kinetic studies sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 77 publications
1
16
0
Order By: Relevance
“…Bacillus subtilis is a Gram-positive bacterium found in soil and is widely used in biological fermentation processes in the food industry. Bacillus subtilis has the ability to produce antimicrobial proteins and a variety of protease activities such as antifungal proteins (5,6), nattokinase (7), pectinase (8) and various bioactive peptides such as antimicrobial peptides and antioxidant peptides etc. (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus subtilis is a Gram-positive bacterium found in soil and is widely used in biological fermentation processes in the food industry. Bacillus subtilis has the ability to produce antimicrobial proteins and a variety of protease activities such as antifungal proteins (5,6), nattokinase (7), pectinase (8) and various bioactive peptides such as antimicrobial peptides and antioxidant peptides etc. (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…More genes with transmembrane transport function means that more protein translocation channels could be synthesized, including those involved in the secretion of lipopeptides, extracellularly resulting in an increase in production [ 16 , 17 ]. A greater number of genes with oxidation–reduction processes reduces the conversion of NADH into NAD to ensure the oxidation–reduction state (NADH/NAD + ) balance at high DO concentrations [ 18 ], resulting in more ATP production with an increased utilization of substrate by bacteria, culminating in an accelerated metabolism to the synthesis of more lipopeptide [ 9 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…BioSol021 resulted in decreased residual concentrations of lactose, glucose and fructose in the cultivation broth at the end of the cultivation, with the consumption rates 30%, 70% and 32%, respectively. Previous studies have shown that the majority of Bacillus strains prefer glucose as the easily fermentable carbon source for biomass growth and lipopeptide production, with a suggested initial glucose concentration in the cultivation medium in the range of 20–40 g/L [ 53 , 54 ]. Lowering the content of carbon sources, as the main contaminants of waste-based media, is significant from the point of view of ecological efficiency of the created bioprocess solution, considering the positive impact on reduction in environmental burden.…”
Section: Resultsmentioning
confidence: 99%